Impact Of Foreign Direct Investment In Indian Retail Sector With Reference To Andhra Pradesh - Ganesh, M.P.Suri; Rao , Tarra Tirupathi (International Journal of Psychosocial Rehabilitation, 2020)
The Government of India was initially very apprehensive of the introduction of the Foreign Direct Investment in the Retail Sector in India. The unorganized retail sector as has been mentioned earlier occupies 98 per cent of the retail sector and the rest 2 per cent is contributed by the organized sector. Hence one reason why the government feared the surge of the Foreign Direct Investments in India was the displacement of labour.There are different viewpoints on the impact of FDI in the retail sector in India, According to one viewpoint, the US evidence is empirical proof to the fact that FDI in the retail sector does not lead to any collapse in the existing employment opportunities. There are divergent views as well. According to the UK Competition Commission, there was mass scale job loss with entry of the hypermarkets brought about by FDI in the UK retail market.This paper highlight is Introduction& Definition of Retail, Division of Retail Industry,FDI Policy inIndia,and impact of FDI in various dimensions.